Prediction of Mechanosensitive Genes in Vascular Endothelial Cells Under High Wall Shear Stress - Shen, Lei; Zhou, Kaige; Liu, Hong; Yang, Jie; Huang, Shuqi; Yu, Fei; Huang, Dongya (Frontiers in Genetics, 2022)
Objective: The vulnerability of atherosclerotic plaques is among the leading cause of ischemic stroke. High wall shear stress(WSS) promotes the instability of atherosclerotic plaques by directly imparting mechanical stimuli, but the specific mechanisms remain unclear. We speculate that modulation of mechanosensitive genes may play a vital role in accelerating plaques development. The purpose of this study was to find mechanosensitive genes in vascular endothelial cells through combining microarray data with bioinformatics technology, and further to explore the underlying dynamics-related mechanisms that cause atherosclerotic plaques progression and destabilization. Methods: Microarray datasets for human vascular endothelial cells under high and normal WSS were retrieved from the Gene Expression Omnibus(GEO) database. Differentially expressed genes(DEGs) were identified through the R language. The performance of enrichment analysis and protein-protein interaction(PPI) network presented the biological function and signaling pathways of DEGs. Hub genes were identified based on the PPI network and validated by GEO datasets. Predicted transcription factor(TF)-genes and miRNAs interaction with potential mechanosensitive genes were identified by Networkanalyst. Results: A total of 260 DEGs,121 up-regulated and 139 down-regulated genes, were screened between high and normal WSS from GSE23289. Ten hub genes and four cluster modules were filtered out based on the PPI network. Enrichment analysis showed that the biological functions of hub genes were mainly involved in responses to unfolded protein and topologically incorrect protein, endoplasmic reticulum stress. Significant pathways associated with hub genes were protein processing in endoplasmic reticulum, antigen processing and presentation. Three out of ten hub genes, ATF3, HSPA6, and DUSP1, were verified in GSE13712. The expression of DUSP1 was higher in the senescent cell under high WSS than that of the young cell. The TF-miRNA-mechanosensitive gene coregulatory network was constructed. Conclusions: In this work, we identified three hub genes, ATF3, HSPA6, and DUSP1, as potential mechanosensitive genes in human blood vessels. DUSP1 was confirmed to be associated with the senescence of vascular endothelial cells. Therefore, these three mechanosensitive genes may have emerged as potential novel targets for the prediction and prevention of ischemic stroke. Furthermore, the TF-miRNA-mechanosensitive genes coregulatory network reveals an underlying regulatory mechanisms and pathways to control disease progression.